Trauma mechanisms and injury patterns in pediatric burn patients. Issue 2 (March 2018) - Moehrlen, Theres; Szucs, Thomas; Landolt, Markus A.; Meuli, Martin; Schiestl, Clemens; Moehrlen, Ueli
Abstract: The objective of this study was to evaluate the frequency, severity, exact patterns and mechanisms of burn injuries in children. The patient records of children with acute burns admitted to the University Children's Hospital of Zurich were retrospectively reviewed over an 11 year period. The age group with the highest risk, were children under the age of five (69%). Boys were overrepresented in all age groups, but the gender imbalance increased with age. Infants and toddlers were mainly injured by scalds and contact burns. Conversely, almost three quarters of injuries over the age of 9 were caused by flame. The majority of scald injuries was a result of pulling down hot liquids. The typical distribution of this accident scenario involved mainly the face, trunk and arms. More than half of all flame injuries occurred due to fire accelerants. 55% of children were passively involved while other children throwing flammable substances into a fire. Most of these injuries involved the face and arms. This study shows that burn etiology is age dependent. Additionally, our results demonstrate the diversity of burn accidents and their resulting injuries. These findings may help better specify target groups and subjects for prevention.